2012
DOI: 10.1093/toxsci/kfs272
|View full text |Cite
|
Sign up to set email alerts
|

CTNNA3 (α-Catenin) Gene Variants Are Associated With Diisocyanate Asthma: A Replication Study in a Caucasian Worker Population

Abstract: Recently, a genome-wide association study (GWAS) conducted in Korean subjects identified four CTNNA3 (alpha-T catenin) single nucleotide polymorphisms (SNPs) (rs10762058, rs7088181, rs1786929, and rs4378283) associated with diisocyanate-induced occupational asthma (DA). The CTNNA3 gene codes for a cadherin involved in formation of stretch-resistant cell-cell adhesions. We conducted a candidate gene association study to replicate these findings in Caucasian workers. Genotyping was performed on DNA using a 5' nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 20 publications
2
50
0
Order By: Relevance
“…Future studies are required to determine whether ␣T-cat KO mice are more susceptible to models of atopic asthma, which also may be better suited to discerning a molecular mechanism owing to their relative robustness compared with TDI asthma models. Overall, our study has validated the genetic associations of ␣T-cat with TDI asthma and lung mechanics (2,11,21,22), suggesting the potential importance of cardiac cell junction function in the development of occupational asthma.…”
Section: Resultssupporting
confidence: 63%
“…Future studies are required to determine whether ␣T-cat KO mice are more susceptible to models of atopic asthma, which also may be better suited to discerning a molecular mechanism owing to their relative robustness compared with TDI asthma models. Overall, our study has validated the genetic associations of ␣T-cat with TDI asthma and lung mechanics (2,11,21,22), suggesting the potential importance of cardiac cell junction function in the development of occupational asthma.…”
Section: Resultssupporting
confidence: 63%
“…Moreover, CTNNA3 SNPs were identified by a GWAS in Korean subjects with diisocyanate-induced occupational asthma (36). Two of the CTNNA3 SNPs identified in the Korean study were subsequently confirmed in a study of Canadian workers with occupational asthma (37). A recent GWAS demonstrated the association between SNP in CTNNA3 and response to glucocorticoid therapy in childhood asthma (38).…”
Section: Discussionmentioning
confidence: 95%
“…The mechanism of OA from diisocyanates remains incompletely understood but sensitization does appear to be mediated by immunologic mechanisms, and there are genetic markers that have been associated with OA from diisocyanates [5053]. Specific IgE antibodies to diisocyanates linked to human albumin have been identified in up to 55% of patients with OA related to diisocyanates [54,55] and have been reported to be very specific for the diagnosis, although having relatively low sensitivity [56].…”
Section: Case Study #2: Isocyanate-induced Asthmamentioning
confidence: 99%